Design, synthesis and evaluation of benzofuran-acetamide scaffold as potential anticonvulsant agent - Shakya Ashok K.; Kamal Mehnaz; Balaramnavar Vishal M.; Bardaweel Sanna K.; Naik Rajashri R.; Saxena Anil K.; Siddiqui H. H. (Acta Pharmaceutica)
A series of N-(2-(benzoyl/4-chlorobenzoyl)-benzofuran- 3-yl)-2-(substituted)-acetamide derivatives (4a-l, 5a-l) was synthesized in good yield. All synthesized compounds were in agreement with elemental and spectral data. The anticonvulsant activity of all synthesized compounds was assessed against the maximal electroshock induced seizures (MES) model in mice. Neurotoxicity was evaluated using the rotarod method. The majority of compounds exhibited anticonvulsant activity at a dose of 30 mg kg-1 body mass during 0.5-4 h, indicating their ability to prevent seizure spread at low doses. Relative to phenytoin, [N-(2-(4-chlorobenzoyl)benzofuran-3-yl)-2-(cyclohexyl( methyl) amino)-acetamide] (5i) and [N-(2-(4-chlorobenzoyl)benzofuran-3-yl)-2-(4-methylpiperidin-1- yl)-acetamide] (5c) demonstrated comparable relative anticonvulsant potency of 0.74 and 0.72, respectively, whereas [(N-(2-(4-chlorobenzoyl)benzofuran-3-yl)-2-(4-(furan-2-carbonyl)-piperazin-1-yl)-acetamide] (5f) exhibited the lowest relative potency of 0.16. The ALD50 of tested compounds ranged from 1.604 to 1.675 mmol kg-1 body mass. The ED50 of synthesized compounds ranged from 0.055 to 0.259 mmol kg-1 (~23.4 to 127.6 mg kg-1) body mass. The pharmacophore mapping of the examined compounds on standard drugs (phenobarbital, phenytoin, ralitolin and carbamazepine) strongly suggests that these compounds may exert their anticonvulsant activity via the same established mechanism as that of known drugs.